Corazón remendado - Tateishi Saito, Víctor (2002)
This work studies the case of a hospital specialized in neurological surgery and how top management in order to improve their services decides to hire three specialized doctors with studies abroad with special considerations causing conflicts between colleagues because the rules do not they were given to everyone equally.